Social Deficits and Repetitive Behaviors Are Improved by Early Postnatal Low-Dose VPA Intervention in a Novel shank3-Deficient Zebrafish Model - Liu, Chunxue; Wang, Yi; Deng, Jingxin; Lin, Jia; Hu, Chunchun; Li, Qiang; Xu, Xiu (Frontiers in Neuroscience, 2021)
Mutations of the SHANK3 gene are found in some autism spectrum disorder (ASD) patients, and animal models harboring SHANK3 mutations exhibit a variety of ASD-like behaviors, presenting a unique opportunity to explore the underlying neuropathological mechanisms and potential pharmacological treatments. The histone deacetylase (HDAC) valproic acid (VPA) has demonstrated neuroprotective and neuroregenerative properties, suggesting possible therapeutic utility for ASD. Therefore, SHANK3-associated ASD-like symptoms present a convenient model to evaluate the potential benefits, therapeutic window, and optimal dose of VPA. We constructed a novel shank3-deficient (shank3ab-/-) zebrafish model through CRISPR/Cas9 editing and conducted comprehensive morphological and neurobehavioral evaluations, including of core ASD-like behaviors, as well as molecular analyses of synaptic proteins expression levels. Furthermore, different VPA doses and treatment durations were examined for effects on ASD-like phenotypes. Compared to wild types (WTs), shank3ab-/- zebrafish exhibited greater developmental mortality, more frequent abnormal tail bending, pervasive developmental delay, impaired social preference, repetitive swimming behaviors, and generally reduced locomotor activity. The expression levels of synaptic proteins were also dramatically reduced in shank3ab-/- zebrafish. These ASD-like behaviors were attenuated by low-dose (5 M) VPA administered from 4 to 8 days post-fertilization (dpf), and the effects persisted to adulthood. In addition, the observed underexpression of grm5, encoding glutamate metabotropic receptor 5, was significantly improved in VPA-treated shank3ab-/- zebrafish. We report for the first time that low-dose VPA administered after neural tube closure has lasting beneficial effects on the social deficits and repetitive behavioral patterns in shank3-deficient ASD model zebrafish. These findings provide a promising strategy for ASD clinical drug development.